Emerging Professional Identity Formation: Exploring Coloniality in the Rehabilitation Professions - Abrahams K; Abdullah A; Pillay M; Kathard H (Oslo and Akershus University College of Applied Sciences, 2022)
This paper explores professional identity formation in undergraduate education. The paper positions professional identity formation within coloniality. A qualitative case study was conducted using critical theory as a guiding conceptual framework. Data collection included document reviews, observations and arts-based research methodologies. We present a case study of a speech-language pathology student, Aqueelah, transitioning from a traditional clinical placement to a learning site which encourages the development of an emerging practice. The paper focuses on how Aqueelah forms her emerging professional identity through her learning. We foreground the concept of “centring the self” as essential in developing patient-centred care and challenge coloniality of being embedded in clinical education. The paper argues that liminal spaces are necessary to allow students to explore different ways of thinking and doing to support new ways of being. The paper advocates for arts-based methodologies and critical reflection as essential pedagogic tools in shaping professional identity.
(c) 2022 The Author/s